2021
DOI: 10.1787/d8bbdcfa-en
|View full text |Cite
|
Sign up to set email alerts
|

Value chains in public marine data

Abstract: Marine data play a crucial role for many scientific disciplines, as well as for very diverse operational services such as fisheries management, environmental planning, marine conservation, weather forecasting, or port management. The information derived from marine data is also increasingly finding its way into a wide and varied range of public policy arenas and private industries. Collecting, distributing and archiving public marine data provide benefits to society at large, however as with all public investm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…The Government of Flanders has, in close cooperation with VLIZ, supported the strategy to embed and foster VLIZ capabilities and infrastructures by their linkage with relevant international networks. The periodic review of VLIZ' performance in this area has confirmed that this strategy has made VLIZ, in particular the VLIZ Marine Data Centre, a strong international partner (IDEAConsult, 2021 [12]).…”
Section: Flanders Marine Institute (Vliz)mentioning
confidence: 94%
See 1 more Smart Citation
“…The Government of Flanders has, in close cooperation with VLIZ, supported the strategy to embed and foster VLIZ capabilities and infrastructures by their linkage with relevant international networks. The periodic review of VLIZ' performance in this area has confirmed that this strategy has made VLIZ, in particular the VLIZ Marine Data Centre, a strong international partner (IDEAConsult, 2021 [12]).…”
Section: Flanders Marine Institute (Vliz)mentioning
confidence: 94%
“…Note: The remaining occupations selected by respondents are (number of unique respondents in parentheses): Marine scientist (geology and geophysics)(12), Digital, data and technology specialist/manager(10), Marine scientist (oceanography, ocean modelling and forecasting) (9),…”
mentioning
confidence: 99%
“…According to the OECD, value chains provide a useful tool for identifying the benefits associated with ocean observations (Jolly et al, 2021). Their case study on value chains in public marine data in the UK found that marine data contributes to better knowledge and improved tools that generate various economic and societal benefits.…”
Section: Background and Contextmentioning
confidence: 99%